Analisis Komunikasi Verbal dan Nonverbal dalam Interaksi Sosial di Instagram - Afiyah Tasya Bitha; Dila Syafira; Hilwa Nafiah Zahra; Indah Purnama; Darmawati Darmawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This research seeks to examine the types and trends of both verbal and nonverbal communication on the social media site Instagram. A qualitative descriptive approach was taken for this study, utilizing methods such as observing the Instagram profiles of public figures, gathering documentation, and conducting interviews with active participants, specifically teenagers and students. The analysis of the data was conducted using an interactive model that included data reduction, presentation, and drawing conclusions. The findings reveal that interactions on Instagram represent a seamless integration of both verbal and nonverbal components. Verbal exchanges are characterized by informal, brief, and vivid language, whereas nonverbal communication, conveyed through emojis and visual symbols, significantly enhances the emotional undertones of the messages. This study concludes that digital technology has enhanced individuals' ability to express themselves in a way that is both efficient and rich in social connotations. Future investigations are recommended to examine the psychological effects of the overuse of nonverbal symbols in digital communication